Le plan de prévention des risques naturels (PPRN) : frein ou catalyseur de l’adaptation des territoires insulaires au changement climatique ? Exemple de Saint-Martin suite à l’ouragan Irma - Audrey Pastel; Pascal Saffache (Études Caribéennes)
In territories exposed to natural risks, the Natural Risk Prevention Plan (PPRN) must take part in helping to adapt to climate change. The first PPRN was developed in 2011 in the French part of St-Martin’s island. It hardly had an impact, as the urbanisation of coastal areas continued, while increasing the vulnerability of the territory. In the aftermath of major hurricane Irma in September 2017, the local authorities launched an improvement of the cyclonic component of the ‘PPRN’. This article aims to explain how the PPRN is experienced as both an obstacle and a catalyst, as a tool in the adaptation to climate change in an island territory; the different prospects depending on the development process of the tool, and how it is understood and appropriated by the stakeholders.